DERIVADOS DA GLUCOSAMINA: SÍNTESE E ATIVIDADE BIOLÓGICA - Santos, Maura Zubiaurre dos (2010)
In the present work, several compounds derived from monosacharide D-Glucosamine were synthetized. These compounds were used successfully against gram-positive and gram-negative microorganisms. In the synthesis of compounds, classical methods in organic chemistry were used.The products were readily prepared from D-Glucosamine in few easy steps. In the first step, we have obtained he imine derivatives 2a or 2b. The resultant imines were protected in the OH groups at C1, C3, C4 and C6 positions with acetyl group. Selective desprotection of C2 aminogroup and coupling with cmnamic acid fford compound 5. All compounds were tested as antimicrobial agents against gram-positive and gram-negative microorganisms. Best results were obtained when compound 2b was used.